Structural insights into the effects of glycerol on ligand binding to cytochrome P450. Issue 1 (5th January 2023) - Bukhdruker, Sergey; Varaksa, Tatsiana; Orekhov, Philipp; Grabovec, Irina; Marin, Egor; Kapranov, Ivan; Kovalev, Kirill; Astashkin, Roman; Kaluzhskiy, Leonid; Ivanov, Alexis; Mishin, Alexey; Rogachev, Andrey; et al.
Abstract : This work shows that glycerol may compromise functional assays and crystallographic studies of pharmacological protein targets, consequently lowering the success rate of drug‐discovery campaigns. Abstract : New antitubercular drugs are vital due to the spread of resistant strains. Carbethoxyhexyl imidazole (CHImi) inhibits cytochrome P450 CYP124, which is a steroid‐metabolizing enzyme that is important for the survival of Mycobacterium tuberculosis in macrophages. The available crystal structure of the CYP124–CHImi complex reveals two glycerol molecules in the active site. A 1.15 Å resolution crystal structure of the glycerol‐free CYP124–CHimi complex reported here shows multiple conformations of CHImi and the CYP124 active site which were previously restricted by glycerol. Complementary molecular dynamics simulations show coherence of the ligand and enzyme conformations. Spectrophotometric titration confirmed the influence of glycerol on CHImi binding: the affinity decreases more than tenfold in glycerol‐containing buffer. In addition, it also showed that glycerol has a similar effect on other azole and triazole CYP124 ligands. Together, these data show that glycerol may compromise structural–functional studies and impede rational drug‐design campaigns.